2011
DOI: 10.1089/hum.2011.069
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation of Cones and Improvement in Visual Function Following Gene Therapy in a Mouse Model of Leber Congenital Amaurosis Caused by Guanylate Cyclase-1 Deficiency

Abstract: Leber congenital amaurosis (LCA) is a severe retinal dystrophy manifesting from early infancy as poor vision or blindness. Loss-of-function mutations in GUCY2D cause LCA1 and are one of the most common causes of LCA, accounting for 20% of all cases. Human GUCY2D and mouse Gucy2e genes encode guanylate cyclase-1 (GC1), which is responsible for restoring the dark state in photoreceptors after light exposure. The Gucy2e(-/-) mouse shows partially diminished rod function, but an absence of cone function before deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 36 publications
4
71
1
Order By: Relevance
“…The clinical success of the RPE65 trials, combined with the increasing number of successful pre-clinical studies using rAAV [18][19][20][21] or lentiviruses, [22][23][24][25][26][27][28] suggest that more retinal gene therapy clinical trials are likely to start in the near future. It is, therefore, crucial to determine the oncogenic potential of these gene delivery vehicles in the context of the retina.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical success of the RPE65 trials, combined with the increasing number of successful pre-clinical studies using rAAV [18][19][20][21] or lentiviruses, [22][23][24][25][26][27][28] suggest that more retinal gene therapy clinical trials are likely to start in the near future. It is, therefore, crucial to determine the oncogenic potential of these gene delivery vehicles in the context of the retina.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no detectable improvement in rod-mediated ERG responses. In contrast, Mihelec et al 60 demonstrated a 65% rescue of cone ERG responses, cone vision and cone survival for up to 6 months, as well as a 35% rescue of rod function, after subretinal administration of an AAV2/8-based vector. Besides the difference in AAV serotype used, there are a number of variables that could account for the difference in efficacy, including the age at intervention, the promoter driving GUCY2D expression and the vector titre administered.…”
Section: Progressive Photoreceptor Defectsmentioning
confidence: 89%
“…For both AIPL1 and GUCY2D, proof-of-concept studies in animal models have shown beneficial effects of subretinal delivery of adeno-associated vectors containing the wild-type coding sequence. [42][43][44] The young age of these patients (10, 2, and 5 years) and the knowledge of their molecular defect identified them as potentially eligible for future gene therapy trials.…”
Section: Discussionmentioning
confidence: 99%